Pelaksanaan Pemilihan Kepala Desa Tahun 2015 Di Desa Dagan Kecamatan Bobotsari Kabupaten Purbalingga Berdasarkan Peraturan Menteri Dalam Negeri Nomor 112 Tahun 2014 - P., Catur Teguh; Suhardiyanto, Andi; Setiajid, Setiajid (Unnes Political Science Journal, 2017)
The village head is the figure of village leaders who have a very large role in leading the organization of village government, fostering the lives of villagers maintain peace and order in rural communities. Therefore, in selecting candidates for village chief should be selective and meets the requirements specified in the Regulation No. 112 of 2014. The purpose of this study is to investigate the implementation of village chief by Regulation No. 112 of 2014 on the election of village chief Dagan. This study used descriptive qualitative approach by using interactive analysis. The research location is in the village of Dagan Sub Bobotsari Purbalingga district. The focus of research is centered on the election of village chief in the village of Dagan of the stages of preparation, nomination, voting and determination. The results showed that at the early stages of the process of the election preparations village chief Dagan was in accordance with Regulation No. 112 of 2014, the stage of the nomination of the selection process of candidates Village Head up to the selection and administration according Regulation No. 112 of 2014 only on the campaign process is not appropriate regulations are still happening violation. In the voting process until the vote count goes according to Regulation No. 112 of 2014, on the stages of the establishment of the village chief is in conformity Regulation Number 112 of 2014. The existence of violations in the campaign that includes the installation of heads mounted before the appointed time and the distribution of money by the candidate Head the village through the Success team to the public. In term of the orderly administration of the election committee head should be scaled back. For the election of village chief Dagan next period, the Village Chief Election Committee is expected to be more transparent and decisive action, especially against a campaign that is not allowed in the regulations. The committee must remain neutral towards the prosecution of all violations that occur in the process of elections Village Chief. Coherence and transparency of the election committee village chief needed to maintain the integrity of democracy in the election of the chief.